Development of BIM plug-in to verify compliance of Architectural Projects according to Municipal Laws – The Case of Passo Fundo/RS - Haas , Lucas; Silva , Thaísa Leal da (Technical and Scientific Journal Green Cities, 2024)
The construction industry plays a significant role in job creation and the socioeconomic development of cities. However, architects and urban planners face challenges due to the delay in the approval of architectural projects by municipal governments, attributed to the non-compliance of projects with local laws. In this context, this study proposes the use of programming in BIM (Building Information Modeling) software, with the aim of developing a plug-in to assist in the process of approving architectural projects in compliance with the municipal laws and regulations of Passo Fundo-RS. The methodology adopted was based on a thorough literature review, document analysis, and the development of a plug-in prototype for Revit, developed in Dynamo using the Python language. The proposed prototype involves the integration of urban data into Revit to automate the collection of information such as building dimensions, lot areas, setbacks, and other metrics. The results revealed that the implementation of programming routines in BIM, especially for Revit, has the potential to significantly reduce the waiting times for project approvals by the municipal government, improve their compliance with local regulations, and minimize pending issues and rework.